Long-term Consequences of Traumatic Brain Injury in Bone Metabolism - Bajwa, Nikita M.; Kesavan, Chandrasekhar; Mohan, Subburaman (Frontiers in Neurology, 2018)
Traumatic brain injury (TBI) leads to long-term cognitive, behavioral, affective deficits, and increase neurodegenerative diseases. It is only in recent years that there is growing awareness that TBI even in its milder form poses long term health consequences to not only the brain but to other organ systems. Also, the concept that hormonal signals and neural circuits that originate in the hypothalamus play key roles in regulating skeletal system is gaining recognition based on recent mouse genetic studies. Accordingly, many TBI patients have also presented with hormonal dysfunction, increased skeletal fragility, and increased risk of skeletal diseases. Research from animal models suggests that TBI may exacerbate the activation and inactivation of molecular pathways leading to changes in both osteogenesis and bone destruction. TBI has also been found to induce the formation of heterotopic ossification and increased callus formation at sites of muscle or fracture injury through increased vascularization and activation of systemic factors. Recent studies also suggest that the disruption of endocrine factors and neuropeptides caused by TBI may induce adverse skeletal effects. This review will discuss the long-term consequences of TBI on the skeletal system and TBI-induced signaling pathways that contribute to the formation of ectopic bone, altered fracture healing, and reduced bone mass.